Action Plans, Declarations and Other Agenda Setting Documents in International Development Interventions: An Indicator to Assure Professionalism - Lempert, David (Momentum Quarterly, 2014)
This article offers an easy-to-use indicator to measure whether “action plans”, international declarations, “master plans”, “country plans”, “country strategies”, “legal frameworks”, and other documents commonly generated in international “aid” interventions meet professional and development standards for truly self-activating, feasible plans in compliance with international law and objectives. Use of this indicator suggests that most of the plans and international declarations that are said to be supported by “developing” countries are created by donors as a means of promoting their own agendas, public relations, and fundraising strategies, with plans that are little indication of “action” or “commitment” or, alternatively, that are designed to be effective but are not in compliance with international law and objectives and are more likely to be an abuse of processes and a corruption of professionalism on both sides. The indicator can be used as an accountability tool to spot and counter these abuses. The piece uses the U.N. Declaration Against Corruption and Bribery in International Commercial Transactions as a case study.
Keywords: Planning; Development; Aid; Globalization; management; United Nations declarations; implementation; strategy; international law